Improved determination of the width of the top quark - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Aoki, M.; Askew, A.; Ratoff, P. N.; et al. (Amer Physical Soc, 2012)
We present an improved determination of the total width of the top quark, Gamma(t), using 5.4 fb(-1) of integrated luminosity collected by the D0 Collaboration at the Tevatron p (p) over bar Collider. The total width Gamma(t) is extracted from the partial decay width Gamma(t -> Wb) and the branching fraction B(t -> Wb). Gamma(t -> Wb) is obtained from the t-channel single top-quark production cross section and B(t -> Wb) is measured in t (t) over bar events. For a top mass of 172.5 GeV, the resulting width is Gamma(t) = 2.00(-0.43)(+0.47) GeV. This translates to a top-quark lifetime of tau(t) = (3.29(-0.63)(+0.90)) x 10(-25) s. We also extract an improved direct limit on the Cabibbo-Kobayashi-Maskawa quark-mixing matrix element 0.81 < vertical bar V-tb vertical bar <= 1 at 95% C.L. and a limit of vertical bar V-tb'vertical bar < 0.59 for a high-mass fourth-generation bottom quark assuming unitarity of the fourth-generation quark-mixing matrix.